Which Clinicopathologic Parameters Suggest Primary Resistance to Palbociclib in Combination With Letrozole as the First-Line Treatment for Hormone Receptor-Positive, HER2-Negative Advanced Breast Cancer? - Kim, Ji-Yeon; Oh, Jung Min; Park, Yeon Hee; Ahn, Jin Seok; Im, Young-Hyuck (Frontiers in Oncology, 2021)
In this study, we evaluated clinical parameters to predict primary resistance of palbociclib in combination with endocrine therapy as the first-line treatment in patients with hormone receptor (HR)+, human epidermal growth factor receptor 2 (HER2) metastatic breast cancer (MBC). We performed data analysis of patients diagnosed with HR+, HER2- MBC who received palbociclib plus letrozole as the first-line treatment in the metastatic setting from the clinical data warehouse (CDW) in Samsung Medical Center. In this study, 305 patients were included in final data analysis. The median follow-up duration was 31 months, and we observed 123 cases of disease progression. Median progression-free survival (PFS) was 28.7 months, and 38 patients (12.5%) had less than a 6-month PFS. Multivariate analysis suggested that primary resistance to adjuvant endocrine therapy (ET) (hazard ratio: 1.91), presence of liver metastasis (hazard ratio: 2.17), initial elevation of serum CA-15-3 (hazard ratio: 1.99), weak positivity of estrogen receptor (ER) (hazard ratio: 2.28), Ki-67 3+ or 4+ (hazard ratios: 2.58 and 10.28), and presence of BRCA2 mutation (hazard ratio: 9.59) were associated with short PFS duration. A further prediction model was developed with data from 256 patients and 33 cases of disease progression in 6 months. This model included five factors, primary resistance to adjuvant ET (odds ratio[OR]: 1.14), liver metastasis (OR: 1.56), initial CA-15-3 elevation (OR: 1.51), weak ER expression (OR: 2.22), and BRCA2 mutation (OR: 2.85), and the area under the receiver operating characteristic curve was 0.842 (95% CIs: 0.775, 0.909; p<0.001). Finally, we divided into four risk groups according to prediction model with the five risk factors. These four groups had different PFS (p<0.001) and primary resistance of palbociclib with letrozole (OR of group 2 vs. group 1[ref]: 2.18 [p=0.002], OR of group 3: 3.91 [p<0.001] and OR of group 4: 4.25[p<0.001]). We developed a prediction model of primary resistance to palbociclib with letrozole as the first-line treatment for HR+, HER2- MBC. Our prediction model might be helpful for considering the first-line treatment strategies. Further well-designed clinical trials would be warranted to validate our prediction model.